Control structure design for optimal operation of heat exchanger networks - Lersbamrungsuk, Veerayut; Srinophakun, Thongchai; Narasimhan, Sridharakumar; Skogestad, Sigurd (AIChE journal, 2008)
When only single bypasses and utility duties are used as manipulations, optimal operation of heat exchanger networks (HENs) can be categorized as an active constraint control problem. This work suggests a simple split-range control scheme to implement the optimal operation. For a given HEN and information about the disturbances, the corresponding control structure can be found by solving an integer-linear programming (ILP) problem with two objective functions providing optimal split-range pairs (for tracking active constraints during the operation) and appropriate control pairings (for fast control action). A HEN case study is used to demonstrate the application of the proposed design technique. Dynamic simulation shows the ability to provide the optimal operation of the obtained control structure. © 2007 American Institute of Chemical Engineers AIChE J, 2008